Transmitter dan Sosialisasi: Peran UNICEF dalam Mencegah Perdagangan Anak Perempuan di India - Imelda Chania; Haiyyu Darman Moenir (Andalas Institute of International Studies, 2021)
This research attempts to describe the role of UNICEF in preventing cases of trafficking of girls in India through the Country Program Action Plan (CPAP) 2013-2017. This is important because of the patriarchal culture in the social fabric of Indian society and the high level of poverty, which drives the trafficking of girls. Besides, this program is also the result of the collaboration between the Indian government and UNICEF in preventing the trafficking of girls in India. This study uses the concept of norm diffusion to answer research questions. A qualitative method with a descriptive-analytical approach applied in this research method. This research shows UNICEF's role in India as a forum to transmit the idea of ​​child protection to Indians, as well as to socialize the beliefs and norms of protecting girls to the Indian government so that rules and policies are in line with the ideas and norms.